Pengaruh Model Pembelajaran STAND (Student Team Achievement Divisions) Terhadap Kemampuan Menulis Cerpen Siswa Kelas XI SMA Negeri 1 Sutera - Ririn, Marta Ririn Putri; Ramadhanti, Dina; Wahyuni Sari, Asri (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
The purpose of this study was to describe how the Student Team Achievement Divisions (STAD) model influences the ability to write short stories for class XI students of SMA Negeri Sutera. This type of research is quantitative using experimental methods. The population in this study were class XI students of SMA Negeri Sutera. The design of this research is One Group Pretest-Posttest Design. The sample in this study were 26 students of class XI at SMA Negeri 1 Sutera. The data in this study were scores of skills in writing short story texts before and after using the Student Team Achievement Divisions (STAD) model for students of XI SMA Negeri 1 Sutera. The results of this study were first, the ability to write short stories for class XI students of SMA N 1 Sutera before using the Student Team Achievement Division (STAD) model obtained an average score of 61.11 in the range of 56-65% with the qualification that is Enough (C). Second, the ability to write short stories for class XI students of SMA Negeri 1 Sutera after using the Student Team Achievement Division model obtained an average score of 76.49 in the 76-85% range with good qualifications (B). Third, based on the t-test there is an effect of the Student Team Achievement Division model on the ability to write short stories for class XI students of SMA Negeri 1 Sutera because tcount = 4.40 and ttable = 1.71 The criteria for testing t is accepted if tcount> ttable, in other words H1 is accepted and H0 is rejected. Thus the Student Team Achievement Divisions (STAD) model can be used in learning to write short stories.